Pemanfaatan Metode Talaqqi Untuk Memperbaiki Cara Membaca Al-Qur’an Pada Anak-Anak Di Rumah Tahfidz Tadzkia Tanjung Sari, Medan - Syahputri, Diana; Zahriani JF, Nurul (EL-EMIR INSTITUTE, 2025)
This study aims to describe the application of the talaqqi method to improve children's Quranic recitation skills at the Tadzkia Tanjung Sari Tahfidz House in Medan. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation from administrators, tahfidz teachers, and students. The results indicate that the talaqqi method is implemented through three main stages: verse recitation by the teacher, practice by students, and direct correction of reading errors. The application of this method has proven effective in improving pronunciation accuracy, understanding of Tajweed rules, and fluency in Quranic recitation. Furthermore, the talaqqi method also builds emotional closeness between teachers and students, thus creating an interactive, comfortable, and religious learning atmosphere. Supporting factors for the implementation of talaqqi include a conducive learning environment, teacher-student closeness, and a consistent lesson schedule. Inhibiting factors include differences in basic abilities between students, limited time, and a lack of learning resources.